Converting biomass into bio-asphalt – a review - Putra Jaya, Ramadhansyah; Z.Y., Mahssin; Norhidayah, Abdul Hassan; Haryati, Yaacob; Mohd Hafiz, Puteh; Che Ros, Ismail; M., Mohammad Zainol; Mohd Zul Hanif, Mahmud (IOP Publishing Ltd, 2021)
The partial substitution of bio-binder for petroleum asphalt binder is possible in the pavement application. Biomass commonly employed renewable energy origin is normally a raw substance used for the production of bio-binder, which includes palm oil, microalgae, soybean oil, vegetable oil, engine oil residue, grape remains, swine waste and many others. This review addresses the diverse bio-oils produced from different biomasses, followed by the properties of bio-oils and performance of bio-asphalt. This review also emphasises on the hydrothermal processing of biomass and the parameters affecting the quality and quantity of the yield for the use in asphalt. Notably, hydrothermal processing is a crucial thermochemical converting procedure employed on biomass into materials or biofuel. Following the aimed products, such as bio-gas, bio-oil, or bio-carbon, the variables selected during the operation (pressure, temperature, and time) is very critical. A notable impact has been placed in assessing a wide range of biomass supplies for hydrothermal processing due to the suitability of the operation for any biomass category. Provided that the majority of the biomass supplies are highly moisturised, the hydrothermal operation is the most efficacious method of processing the supplies. On the other hand, the physical, and rheological properties of the biobinders or bio-asphalt were highlighted and discussed. Majority of the bio-oils were found to improve the low-temperature performance, but reduce the resistance against deformation at high temperature of the bio-asphalt. It was also suggested that further studies should emphasise on the interaction between the asphalt matrix and bio-oils added at the microscale.